2013
DOI: 10.1002/esp.3406
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of transient topographic disequilibrium in a landward passive margin river system: knickpoints and paleo‐landscapes of the New River basin, southern Appalachians

Abstract: The upper New River basin of the southern Appalachian Mountains, a major tributary of the modern Ohio River, represents the unglaciated headwaters of the Tertiary Teays River system of eastern North America. Dating of relict fluvial gravels have suggested that New River incision may be outpacing lowering of the surrounding uplands, but physical evidence of transient topographic disequilibrium has yet to be identified. We use focused topographic analysis of the upper New River basin to delineate a perched, low‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…Seismic data suggest tens of millions of years ago a hidden hotspot may have passed through northern Virginia although the effect of such a passage on escarpment topography is uncertain (Chu et al , ). Field observations as well as numerical landscape analysis and modeling suggest that the area around the escarpment is significantly and episodically modified by drainage capture events and large‐scale recent uplift (dynamic topography) likely driven by mantle processes (Prince et al , , ; Prince and Spotila, ; Gallen et al , ; Rowley et al , ; Miller et al , ; Schmandt and Lin, ; Naeser et al , ). Such capture events transiently increase the rate of basin‐scale erosion and escarpment retreat in specific areas along escarpment strike as base‐level falls rapidly and incision propagates upstream.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seismic data suggest tens of millions of years ago a hidden hotspot may have passed through northern Virginia although the effect of such a passage on escarpment topography is uncertain (Chu et al , ). Field observations as well as numerical landscape analysis and modeling suggest that the area around the escarpment is significantly and episodically modified by drainage capture events and large‐scale recent uplift (dynamic topography) likely driven by mantle processes (Prince et al , , ; Prince and Spotila, ; Gallen et al , ; Rowley et al , ; Miller et al , ; Schmandt and Lin, ; Naeser et al , ). Such capture events transiently increase the rate of basin‐scale erosion and escarpment retreat in specific areas along escarpment strike as base‐level falls rapidly and incision propagates upstream.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if thermochronologic data show no time–distance relationship across the lowlands and cosmogenic data indicate millennial‐timescale rates of retreat for an inland escarpment that are too slow to accommodate the distance the escarpment has moved over the time interval since rifting began, then the concept of an escarpment continuously retreating at one rate over time is not plausible. In such a case, the erosion responsible for the inland position of the escarpment either must have occurred rapidly, soon after rifting, such that a period of relative erosional stability (post retreat) coincides with the integration time of the thermochronologic data or erosion occurs episodically, through drainage capture and rapid back‐wearing of drainage divides (Prince et al , , ; Prince and Spotila, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coweeta is underlain by high‐grade metamorphic rocks, primarily biotite and quartz diorite gneisses, with minor schists and metasedimentary rocks that have been strongly folded and faulted throughout the basin (Hatcher, ). Authors have suggested that this area may diverge from steady state due to rejuvenation of uplift in the Miocene (Gallen et al, ) or drainage reorganization associated with escarpment retreat (Prince & Spotila, ). However, erosion rates measured in the basin are consistent with rates measured in the nearby Great Smoky Mountains, suggestive of a mountain range approaching steady state.…”
Section: Coweeta North Carolinamentioning
confidence: 99%
“…As to the culprit of this incision of the upper New River, their interpretation points out a well‐known glacially‐forced drop in landward base level, linked with the reorganization of the Teays River system along the margin of advancing late Pliocene and Pleistocene ice sheets. The study of Prince and Spotila () thus highlights the potential of far‐field long‐lived drainage basin reorganisation over distances of hundreds of kilometers away from perturbations and over long periods of time after perturbations. This finding is well in line with current models of dynamic river basin evolution as recently put forth in the work of Willett et al (), for instance.…”
Section: Tectonics and Climate Into Landscapesmentioning
confidence: 99%